Mercy Watson is missing! : tales from Deckawoo Drive, volume seven - DiCamillo, Kate; Van Dusen, Chris (Candlewick Press, 2023)
While bumbling PI Percival Smidgely tries to find missing pig Mercy Watson, a trio of clever neighborhood sleuths follow a trail of hoof prints - and a delicious aroma - to recover their porcine wonder, in this uproariously funny, extra-special series finale.
Keywords: Swine -- Fiction; Pigeons -- Fiction; Private investigators -- Fiction; Humorous fiction; Animal fiction